Strategies For Achieving Under School (ATS) Through Smart Indonesia Programs (PIP) - Herlinawati Syaukat; Arie Budi Susanto (usat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2019)
This study aims to: 1) Data Collection of Non-School Children (ATS), 2) Factors that cause ATS and return to school, 3) Attempts and motivation of ATS back to school. Using qualitative and quantitative methods with purposive sampling. The ATS data collection is constrained by synchronization of data from the district / city starting from the village and kelurahan level to facilitate verification of PIP data on children who have not yet received access to education in Surabaya City and Padang City according to the target because HR / data is less than the location and difficult geographical conditions, while the data collection time is limited. For this reason, a one-door mechanism is needed for data synchronization. Whereas the regions which were well recorded even exceeded the target achievement due to the area being the ATS enclave was Bogor Regency and Gorontalo Regency. The most common factors causing ATS are economic, geographical, social environment influences, and lack of self motivation in students. Efforts are being made so that ATS can return to education, among others; 1). The government and regional government guarantee that registered ATS will receive financial assistance and can continue schooling again; 2). Provide a learning place for ATS of at least one village, one study group with adequate facilities; 3). To provide guidance or assistance to ATS to motivate the ATS to get education services again; 4). Bring a psychologist or motivator to encourage ATS to come to learning; 5). Persuasive approach both to ATS and to parents; 6). Bringing ATS alumni who are successful and successful as an example / figure that is expected to generate enthusiasm and motivation for ATS to succeed as its alumni.